Effect of Rhizopus Oryzae Fermentation on Kenaf-based Polylactic Acid’s Monomer - Mohd Nasir, Nur Aimi; Mustafa Kamalbahrin, Mohd Adlan; Mohamed, Nurhafizah Seeni; Anuar, Hazleen; Mel, Maizirwan; Othman, Rashidi (IIUM Press, 2011)
Kenaf biomass is the potential as raw materials used to produce polylactic acid’s monomer which is lactic acid via fermentation by Rhizopus oryzae. Kenaf biomass’ structure is complex due to its lignin and cellulose content. This matter had encouraged it to undergo pre- treatment process as the initial step before fermentation process can be done. In this paper, kenaf biomass was treated with dilute sulphuric acid (H2SO4) to hydrolyze the cellulose content in it as well as to convert the cellulose into glucose- a carbon source for Rhizopus to grow. Then, the fermentation process was carried out in shake flask for 3 days at pH 6. Several conditions for fermentation process had been chosen which were 25oC at 150 rpm, 25 oC at 200 rpm, 37 oC at 150 rpm and 37oC at 200 rpm. In this fermentation process, 0.471 g/L, 0.428 g/L, 0.444 g/L and 0.38 g/L of lactic acid was produced respectively. Sample at 25oC at 200 rpm produced maximum amount of lactic acid compared to others.